A comparative study of biochar, multiwalled carbon nanotubes and graphitized carbon black as QuEChERS absorbents for the rapid determination of six triazole fungicides by UPLC-MS/MS. Issue 3 (19th February 2019) - Cao, Junli; Zheng, Yunxi; Kaium, Abdul; Liu, Xingang; Xu, Jun; Dong, Fengshou; Wu, Xiaohu; Zheng, Yongquan
ABSTRACT: A rapid, effective and sensitive method to quantitatively determine six fungicide residue was developed using ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC–MS/MS). The target compounds were extracted by using acetonitrile and the sorbent used for clean-up in this modified QuEChERS analytical method were biochar, multiwalled carbon nanotubes (MWCNT) and graphitized carbon black (GCB). Results indicated that the MWCNT (10 mg) was the most effective sorbent in removing pigment. This method was validated on spinach, tomato, cucumber, celery, lettuce, rape, pakchoi, romaine lettuce and eggplant matrices spiked at three concentration levels of 0.01, 0.1 and 1 mg kg −1 . It exhibited recoveries between 73.1% and 118.2% with RSD values below 20%. Matrix-matched calibrations were performed with the coefficients of determination >0.9901 between concentration levels of 0.01–1 mg kg −1 . The limit of quantity (LOQ) for six pesticides ranged from 0.0036 to 0.011 mg kg −1 . The developed method was satisfactorily applied to determine pesticide residues in market vegetable samples.